Photocatalyzed syntheses of phenanthrenes and their aza-analogues. A review - Del Tito, Alessandra; Abdulla, Havall Othman; Ravelli, Davide; Protti, Stefano; Fagnoni, Maurizio (Beilstein Journal of Organic Chemistry, 2020)
Phenanthrenes and their aza-analogues have important applications in materials science and in medicine. Aim of this review is to collect recent reports describing their synthesis, which make use of radical cyclizations promoted by a visible light-triggered photocatalytic process.
Keywords: phenanthrenes; phenanthridines; photocatalysis; radicals; visible light

(untitled) - Kovács, A.; Vasas, A.; Hohmann, J. (Phytochemistry, 2008)

(untitled) - Kim, H.; Schulte, N.; Zhou, G.; Müllen, K.; Laquai, F. (Adv. Mater., 2011)

(untitled) - Raouafi, S.; Aloui, F.; Raouafi, A.; Hassine, B. B. (C. R. Chim., 2017)

(untitled) - Jiang, H.; Ren, Y.; Zhang, W.; Wu, Y.; Socie, E. C.; Carlsen, B. I.; Moser, J.-E.; Tian, H.; Zakeeruddin, S. M.; Zhu, W.-H.; Grätzel, M. (Angew. Chem., Int. Ed., 2020)

(untitled) - Peña, D.; Pérez, D.; Guitián, E.; Castedo, L. (Org. Lett., 1999)

(untitled) - Hu, J.-T.; Zheng, B.; Chen, Y.-C.; Xiao, Q. (Org. Chem. Front., 2018)

(untitled) - Fürstner, A.; Mamane, V. (J. Org. Chem., 2002)

(untitled) - Matsuda, T.; Kato, K.; Goya, T.; Shimada, S.; Murakami, M. (Chem. – Eur. J., 2016)

(untitled) - Ye, F.; Shi, Y.; Zhou, L.; Xiao, Q.; Zhang, Y.; Wang, J. (Org. Lett., 2011)

(untitled) - Jørgensen, K. B. (Molecules, 2010)

(untitled) - Protti, S.; Artioli, G. A.; Capitani, F.; Marini, C.; Dore, P.; Postorino, P.; Malavasi, L.; Fagnoni, M. (RSC Adv., 2015)

(untitled) - Harayama, T.; Akamatsu, H.; Okamura, K.; Miyagoe, T.; Akiyama, T.; Abe, H.; Takeuchi, Y. (J. Chem. Soc., Perkin Trans. 1, 2001)

(untitled) - Yang, X.-J.; Miao, F.; Yao, Y.; Cao, F.-J.; Yang, R.; Ma, Y.-N.; Qin, B.-F.; Zhou, L. (Molecules, 2012)

(untitled) - Larsen, A. K.; Grondard, L.; Couprie, J.; Desoize, B.; Comoe, L.; Jardillier, J.-C.; Riou, J.-F. (Biochem. Pharmacol., 1993)

(untitled) - Bouquet, J.; Rivaud, M.; Chevalley, S.; Deharo, E.; Jullian, V.; Valentin, A. (Malar. J., 2012)

(untitled) - Morgan, G. T.; Walls, L. P. (J. Chem. Soc., 1931)

(untitled) - Tumir, L.-M.; Radić Stojković, M.; Piantanida, I. (Beilstein J. Org. Chem., 2014)

Science of Synthesis - Keller, P. A. (Georg Thieme Verlag KG, 2004)

(untitled) - Lysén, M.; Kristensen, J. L.; Vedsø, P.; Begtrup, M. (Org. Lett., 2002)

(untitled) - Zhang, L.; Ang, G. Y.; Chiba, S. (Org. Lett., 2010)

(untitled) - Fan, J.; Li, L.; Zhang, J.; Xie, M. (Chem. Commun., 2020)

(untitled) - Candito, D. A.; Lautens, M. (Angew. Chem., Int. Ed., 2009)

(untitled) - Jaiswal, Y.; Kumar, Y.; Pal, J.; Subramanian, R.; Kumar, A. (Chem. Commun., 2018)

Photoorganocatalysis in organic synthesis - Fagnoni, M.; Protti, S.; Ravelli, D. (World Scientific Publishing Europe Ltd., 2019)

Visible Light Photocatalysis in Organic Chemistry - Stephenson, C. R. J.; Yoon, T. P.; MacMillan, D. W. C. (Wiley-VCH, 2018)

Chemical Photocatalysis - Koenig, B. (De Gruyter, 2013)

(untitled) - Albini, A.; Fagnoni, M. (Green Chem., 2004)

Eco-friendly synthesis of fine chemicals - Protti, S.; Manzini, S.; Fagnoni, M.; Albini, A. (The contribution of photochemistry to green chemistry, 2009)

Applied Photochemistry: When Light Meets Molecules - Ravelli, D.; Protti, S.; Fagnoni, M. (Application of visible and solar light in organic synthesis, 2016)

Encyclopedia of Radicals in Chemistry, Biology and Materials - Chatgilialoglu, C.; Studer, A. (John Wiley & Sons, Ltd, 2012)

(untitled) - Ravelli, D.; Protti, S.; Fagnoni, M. (Chem. Rev., 2016)

(untitled) - Goddard, J.-P.; Ollivier, C.; Fensterbank, L. (Acc. Chem. Res., 2016)

(untitled) - Pitre, S. P.; Weires, N. A.; Overman, L. E. (J. Am. Chem. Soc., 2019)

(untitled) - Xiong, T.; Zhang, Q. (Chem. Soc. Rev., 2016)

(untitled) - Kärkäs, M. D. (ACS Catal., 2017)

(untitled) - Zlot-skii, S. S.; Kochinashvili, M. V.; Rakhmankulov, D. L. (Chem. Heterocycl. Compd., 1993)

(untitled) - Russell Bowman, W.; Fletcher, A. J.; Potts, G. B. S. (J. Chem. Soc., Perkin Trans. 1, 2002)

(untitled) - Naito, T. (Pure Appl. Chem., 2008)

Free-Radical Synthesis and Functionalization of Heterocycles - Crespi, S.; Fagnoni, M. (Photocatalyzed Formation of Heterocycles, 2018)

(untitled) - Cano-Yelo, H.; Deronzier, A. (J. Chem. Soc., Perkin Trans. 2, 1984)

(untitled) - Xiao, T.; Dong, X.; Tang, Y.; Zhou, L. (Adv. Synth. Catal., 2012)

(untitled) - Chatterjee, T.; Lee, D. S.; Cho, E. J. (J. Org. Chem., 2017)

(untitled) - Nagode, S. B.; Kant, R.; Rastogi, N. (Eur. J. Org. Chem., 2018)

(untitled) - Lei, J.; Huang, J.; Zhu, Q. (Org. Biomol. Chem., 2016)

(untitled) - Ryu, I.; Sonoda, N.; Curran, D. P. (Chem. Rev., 1996)

(untitled) - Yang, X.-L.; Chen, F.; Zhou, N.-N.; Yu, W.; Han, B. (Org. Lett., 2014)

(untitled) - Fang, H.; Zhao, J.; Ni, S.; Mei, H.; Han, J.; Pan, Y. (J. Org. Chem., 2015)

(untitled) - Rohe, S.; McCallum, T.; Morris, A. O.; Barriault, L. (J. Org. Chem., 2018)

(untitled) - Jiang, H.; Cheng, Y.; Wang, R.; Zheng, M.; Zhang, Y.; Yu, S. (Angew. Chem., Int. Ed., 2013)

(untitled) - Zhu, Z.-F.; Zhang, M.-M.; Liu, F. (Org. Biomol. Chem., 2019)

(untitled) - Wang, L.; Ding, Q.; Li, X.; Peng, Y. (Asian J. Org. Chem., 2019)

(untitled) - Fu, W.; Zhu, M.; Xu, C.; Zou, G.; Wang, Z.; Ji, B. (J. Fluorine Chem., 2014)

(untitled) - Wang, S.; Jia, W.-L.; Wang, L.; Liu, Q. (Eur. J. Org. Chem., 2015)

(untitled) - Zhu, M.; Fu, W.; Zou, G.; Xu, C.; Wang, Z. (J. Fluorine Chem., 2015)

(untitled) - Zhang, Z.; Tang, X.; Dolbier, W. R., Jr (Org. Lett., 2015)

(untitled) - Sun, X.; Yu, S. (Org. Lett., 2014)

(untitled) - Wang, R.; Jiang, H.; Cheng, Y.; Kadi, A. A.; Fun, H.-K.; Zhang, Y.; Yu, S. (Synthesis, 2014)

(untitled) - Rong, J.; Deng, L.; Tan, P.; Ni, C.; Gu, Y.; Hu, J. (Angew. Chem., Int. Ed., 2016)

(untitled) - Fang, J.; Shen, W.-G.; Ao, G.-Z.; Liu, F. (Org. Chem. Front., 2017)

(untitled) - Li, J.; Caiuby, C. A. D.; Paixão, M. W.; Li, C.-J. (Eur. J. Org. Chem., 2018)

(untitled) - Tang, X.; Song, S.; Liu, C.; Zhu, R.; Zhang, B. (RSC Adv., 2015)

(untitled) - Wei, J.; Gu, D.; Wang, S.; Hu, J.; Dong, X.; Sheng, R. (Org. Chem. Front., 2018)

(untitled) - Gu, L.; Jin, C.; Liu, J.; Ding, H.; Fan, B. (Chem. Commun., 2014)

(untitled) - Li, X.; Liang, D.; Huang, W.; Sun, H.; Wang, L.; Ren, M.; Wang, B.; Ma, Y. (Tetrahedron, 2017)

(untitled) - Xiao, T.; Li, L.; Lin, G.; Wang, Q.; Zhang, P.; Mao, Z.-w.; Zhou, L. (Green Chem., 2014)

(untitled) - Liu, S.; Pan, W.; Wu, S.; Bu, X.; Xin, S.; Yu, J.; Xu, H.; Yang, X. (Green Chem., 2019)

(untitled) - Li, C.-X.; Tu, D.-S.; Yao, R.; Yan, H.; Lu, C.-S. (Org. Lett., 2016)

(untitled) - Singh, M.; Yadav, A. K.; Yadav, L. D. S.; Singh, R. K. P. (Synlett, 2018)

(untitled) - Yuan, Y.-C.; Liu, H.-L.; Hu, X.-B.; Wei, Y.; Shi, M. (Chem. – Eur. J., 2016)

(untitled) - Feng, S.; Li, T.; Du, C.; Chen, P.; Song, D.; Li, J.; Xie, X.; She, X. (Chem. Commun., 2017)

(untitled) - Zhou, H.; Deng, X. Z.; Zhang, A. H.; Tan, R. X. (Org. Biomol. Chem., 2016)

(untitled) - Fu, W.; Zhu, M.; Xu, F.; Fu, Y.; Xu, C.; Zou, D. (RSC Adv., 2014)

(untitled) - Natarajan, P.; Kumar, N.; Sharma, M. (Org. Chem. Front., 2016)

(untitled) - Natarajan, P.; Chuskit, D.; Priya (Green Chem., 2019)

(untitled) - Chatterjee, T.; Choi, M. G.; Kim, J.; Chang, S.-K.; Cho, E. J. (Chem. Commun., 2016)

(untitled) - Yin, W.; Wang, X. (New J. Chem., 2019)

(untitled) - Jiang, H.; An, X.; Tong, K.; Zheng, T.; Zhang, Y.; Yu, S. (Angew. Chem., Int. Ed., 2015)

(untitled) - An, X.-D.; Yu, S. (Org. Lett., 2015)

(untitled) - Liu, X.; Qing, Z.; Cheng, P.; Zheng, X.; Zeng, J.; Xie, H. (Molecules, 2016)

(untitled) - Sun, J.; He, Y.; An, X.-D.; Zhang, X.; Yu, L.; Yu, S. (Org. Chem. Front., 2018)

(untitled) - Sun, X.; Yu, S. (Chem. Commun., 2016)

(untitled) - Qin, H.-T.; Wu, S.-W.; Liu, J.-L.; Liu, F. (Chem. Commun., 2017)

(untitled) - Mao, L.-L.; Zheng, D.-G.; Zhu, X.-H.; Zhou, A.-X.; Yang, S.-D. (Org. Chem. Front., 2018)

(untitled) - Mao, L.-L.; Quan, L.-X.; Zhu, X.-H.; Ji, C.-B.; Zhou, A.-X.; Chen, F.; Zheng, D.-G. (Synlett, 2019)

(untitled) - Zhu, M.; Fu, W.; Guo, W.; Tian, Y.; Wang, Z.; Ji, B. (Org. Biomol. Chem., 2019)

(untitled) - Gao, F.; Yang, C.; Ma, N.; Gao, G.-L.; Li, D.; Xia, W. (Org. Lett., 2016)

(untitled) - Liu, X.; Wu, Z.; Zhang, Z.; Liu, P.; Sun, P. (Org. Biomol. Chem., 2018)

(untitled) - Li, X.; Fang, X.; Zhuang, S.; Liu, P.; Sun, P. (Org. Lett., 2017)

(untitled) - Yu, Y.; Cai, Z.; Yuan, W.; Liu, P.; Sun, P. (J. Org. Chem., 2017)

(untitled) - Yu, Y.; Yuan, W.; Huang, H.; Cai, Z.; Liu, P.; Sun, P. (J. Org. Chem., 2018)

(untitled) - Moon, Y.; Jang, E.; Choi, S.; Hong, S. (Org. Lett., 2018)

(untitled) - Usami, K.; Yamaguchi, E.; Tada, N.; Itoh, A. (Eur. J. Org. Chem., 2020)

(untitled) - Zhao, J.; Li, H.; Li, P.; Wang, L. (J. Org. Chem., 2019)

(untitled) - Maiti, D.; Halder, A.; De Sarkar, S. (Adv. Synth. Catal., 2019)

(untitled) - Lu, Y.; Chen, L.; Chen, X.; Yao, M.; Luo, Z.; Zhang, Y. (Synthesis, 2020)